123k views
2 votes
Differentiate with respect to t

Assume x = x(t)
Assume y = y(t)
Assume z = z(t)

x^2 - y^3 + z^4 = 1

User Rupi
by
5.8k points

1 Answer

3 votes

Answer:


\displaystyle 2x(dx)/(dt)-3y^2(dy)/(dt)+4z^3(dz)/(dt)=0

Explanation:

We want to differentiate the equation:


x^2-y^3+z^4=1

With respect to t, where x, y, and z are functions of t.

So:


\displaystyle (d)/(dt)\left[x^2-y^3+z^4\right]=(d)/(dt)\left[1\right]

Implicitly differentiate on the left. On the right, the derivative of a constant is simply zero. Hence:


\displaystyle 2x(dx)/(dt)-3y^2(dy)/(dt)+4z^3(dz)/(dt)=0

User QKWS
by
6.9k points